2019
DOI: 10.1002/jhbp.624
|View full text |Cite
|
Sign up to set email alerts
|

Propofol inhibits pancreatic cancer progress under hypoxia via ADAM8

Abstract: Background To investigate the potential anti-tumoral properties of propofol in pancreatic cancer and elucidate the underlying mechanisms. Methods The relative expression of ADAM metallopeptidase domain 8 (ADAM8) in response to hypoxia in Panc1 cells was analyzed by western blotting. The enzymatic activity was determined by fluorescence release from PEPDAB013 decomposition. Cell growth was measured via cell counting and cell viability was measured using CCK-8 kit. Cell migrative capacity was evaluated by transw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 28 publications
3
28
0
2
Order By: Relevance
“…8 Gao et al demonstrated that propofol suppressed hypoxia-induced cell progression in pancreatic cancer. 26 Consistent with these data, our results indicated that propofol weakened the inhibitory effect of hypoxia on EC cell migration, invasion, and EMT through downregulating HIF-1α level. Therefore, propofol acted as a negative regulator in hypoxia-induced EC cell progression.…”
Section: Discussionsupporting
confidence: 89%
“…8 Gao et al demonstrated that propofol suppressed hypoxia-induced cell progression in pancreatic cancer. 26 Consistent with these data, our results indicated that propofol weakened the inhibitory effect of hypoxia on EC cell migration, invasion, and EMT through downregulating HIF-1α level. Therefore, propofol acted as a negative regulator in hypoxia-induced EC cell progression.…”
Section: Discussionsupporting
confidence: 89%
“…A number of studies have indicated that propofol suppresses the malignancy of a variety of human cancers, such as hepatocellular carcinoma (HCC) [23] , breast cancer [24] , and lung cancer [25] . Moreover, some studies have suggested a possible correlation between propofol and chemotherapy, though the results are unde ned [26] .Previous studies conducted by our research group have shown that propofol inhibits pancreatic tumor growth via ADAM8 [10] and further found that propofol speci cally inhibited ADAM8 expression and activation in response to hypoxia in pancreatic cancer [11] . The results of present study are consistent with these previous reports.…”
Section: Discussionmentioning
confidence: 90%
“…Once upregulated, ADAM8 is proteolytically active and resultsin enhanced shedding of cell adhesion molecules, cytokine receptors and extracellular matrix (ECM) components [9] . In our previous study, we found that propofol could downregulate ADAM8 expression under hypoxic conditions [10] , which partially inhibits the activity of AMAD8 (this was not observed when compared with the control drug Batimastat, BB-94) [10,11] .For these reasons it is possible that other mechanisms participate in the effect of propofolon pancreatic cancer through ADAM8.…”
Section: Introductionmentioning
confidence: 97%
“…For example, NGFR is the receptor of NGF, which can induce chick CAM neovascularization [46]. Studies have shown that ADAM8 is signi cantly induced by hypoxia and plays a role in the proliferation and migration of endothelial cells during angiogenesis [47,48]. Therefore, we speculate that the enhanced tolerance of Tibetan chicken embryo CAM under hypoxic conditions is ascribed to miRNA-mediated modulation of the related target mRNAs, further regulating HIF, which enables it to maintain hypoxic adaptation via the promotion of angiogenesis and blood circulation.…”
Section: Discussionmentioning
confidence: 99%